The Oxford Ankle Foot Questionnaire for Children: review of development and potential applications. - Morris, C; Doll, H; Wainwright, A; Davies, N; Theologis, T; Fitzpatrick, R (2010)
There is increasing recognition of the credibility and utility of patient reported outcome measures, both in research and as routine quality indicators. This paper reviews the development of a questionnaire for children with foot or ankle problems and integrates the findings from three previously published studies in a cohesive way for the orthotic community. The Oxford Ankle Foot Questionnaire for Children was designed to evaluate the effectiveness of interventions. The development process was conducted in three phases. First the items were devised through focus groups with children affected by foot and ankle problems, and their parents. Second, test versions of child and parent questionnaires were evaluated to enable scales to be developed and tested for validity and reliability. Finally, findings from a prospective study assessing how scores changed over time and/or with treatment supported the longitudinal validity and responsiveness of the scales. The questionnaire offers an inexpensive and expedient means to evaluate the effectiveness of orthoses and other interventions used to treat children's foot or ankle problems. The Oxford Ankle Foot Questionnaire for Children has broad utility both in routine clinical settings, or applied research to evaluate treatment programmes and interventions used in paediatric orthopaedics, trauma and rheumatology.